Analisis Kebutuhan Pengembangan Practical E-Guidebook IPA untuk Mahasiswa UIN Sunan Kalijaga - Ririn Hestiningtyas; Woro Sri Hastuti; Setiawan Edi Wibowo; Sigit Prasetyo (Postgraduate, University of Mataram, 2023)
Practical E-Guidebook is a facility for practicum activities that contains digital-based instructions and information so that students can carry out practicum activities independently. The aim of this research is to analyze the need for practical science e-guidebooks for UIN Sunan Kalijaga students. This research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development research model in the analysis stage. The data collection techniques used in this research were interviews and questionnaires to determine the analysis of students' needs for the Practical E-Guidebook. The aspects analyzed in this research are analysis of independent practicum activities for elementary science learning, analysis of tools and materials in the laboratory in independent practicum activities for elementary science learning, analysis of media availability in independent practicum activities for elementary science learning, analysis of the benefits of the Practical E-Guidebook for science in practicum activities independent Elementary School Science Learning, analysis of the need for innovation in science practicum learning media. This research found that there was an average percentage of 82% with the majority of students stating that the Practical Science E-Guidebook needed to be developed so that the implementation of independent practical activities for students in elementary science learning courses could run in a structured manner and the preparation of reports could be well structured.